Small islands, big challenges - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The International Meeting on Small Island Developing States (SIDS) has a well-organised website, with climate change featuring strongly.